Predictive model estimating the performances of centrifugal pumps used as turbines. (15th July 2016) - Barbarelli, S.; Amelio, M.; Florio, G.
Abstract: A one-dimensional numerical code estimating the performances of centrifugal PATs (pumps used as turbines) is presented. Firstly, the code calculates the geometrical components of the PAT using information provided in manufacturer catalogues. Then, once these parameters are deduced, it calculates the losses and determines the characteristics curves of the PAT. The method was validated by comparing the theoretical curves with some experimental measurements acquired at the Department of Mechanical, Energy and Management Engineering (DIMEG) of the University of Calabria, at the Mechanical Propulsion National Centre (CNPM) in Milan and at the University of Trento (Italy) on PATs working in a range of specific speed from 9 to 65 rpm m 3/4  s −1/2 . The estimation error was comprised in a range of 5 ÷ 20%, generally acceptable for this kind of application. Highlights: A model, predicting the performances of pumps used as turbines, has been presented. The model recreates the geometry of the PAT starting from manufacturers catalogues. The model calculates the curves head-capacity and efficiency-capacity. The Best Efficiency Point (BEP) localisation is well calculated by the model. The Williams indicator validates the model results better than other correlations.